Surfaces functionalized by graphene oxide nanosheets for single cell investigations; Sensors and Actuators B: Chemical; Vol. 255, pt. 2 - Dedelaite L. Lina; Rodriguez (Rodriges) Contreras R. D. Raul David; Andriukonis E. Eivydas; Hietschold M. Michael; Zahn D. R. T. Dietrich; Ramanavicius A. Arunas (2018, 2018)
Title screen